Unveiling the mechanisms of Tianjihuang in hepatocellular carcinoma: a network pharmacology and molecular docking study - Bixing Liang; Wenyu Wu; Fan He; Bing Yang; Dongxin Tang (Discover Oncology)
Abstract Background Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality worldwide, with limited therapeutic options and poor long-term survival. Hypericum japonicum Thunb. (Tianjihuang), a traditional Chinese medicine exhibits promising anticancer properties. This study aims to elucidate the multi-target mechanisms of Tianjihuang in treating HCC using network pharmacology and molecular docking techniques. Methods The active components of Tianjihuang and their targets were retrieved from TCMSP, PubChem, and Swiss Target Prediction databases. HCC-related targets were identified using GeneCard, OMIM, and TTD databases, and overlapping targets were analyzed. Protein–protein interaction (PPI) networks were constructed and analyzed using Cytoscape. Functional enrichment analysis of key targets was performed via GO and KEGG pathways. Kaplan–Meier curves assessed the clinical relevance of core targets, and molecular docking evaluated the binding affinities between Tianjihuang components and key targets. Results Tianjihuang contained seven bioactive components targeting 207 genes, with 77 overlapping HCC-related targets. PPI analysis identified key targets, including AKT1, STAT3, EGFR, and ESR1, which play pivotal roles in HCC pathogenesis. GO and KEGG analysis revealed that Tianjihuang's anti-HCC effects involve multiple biological processes and pathways, such as cell proliferation, apoptosis, and PI3K-Akt signaling. Molecular docking results showed high binding affinities of key components, such as quercetin and gallic acid, with core targets supporting their potential therapeutic effects. Conclusion This study demonstrates that Tianjihuang exerts its anti-HCC effects through a multi-component, multi-target, and multi-pathway mechanism. These findings provide a scientific foundation for the clinical application of Tianjihuang and highlight its potential as a complementary therapy for HCC.